Analyses of Trace Elements, Arsenic (As), Boron (B), Lead (Pb), Strontium (Sr) and Zinc (Zn), in Human Body and their Correlation with Immune Status Against Viral Infections - Tabinda Ijaz, Fayyaz Ahmad, Muhammad Atif, Sajjad Ullah, Ahmed Bilal Waqar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Trace elements have been used since ancient times as a therapeutic agent. However, until recently its use in modern medicine has been restricted to the treatment of a limited number of parasitic infections, but now some evidence is there that they can be helpful in the treatment of a variety of diseases. Aim and Objective: This research was organized to investigate the concentration of trace metals in human blood and their positive effects against viral infection. Methods: Instrumental analysis of the elevated level of metal concentration was performed by Inductively Coupled plasma-optical emission spectroscopy (ICP-OES) and the presence of virus antibodies by Enzyme linked immunosorbent assay (ELISA) and viral load analysis by Real time Polymerase chain reaction (RT-PCR). Results: The Mean±SD of As, B, Pb, Sr and Zn in negative RT-PCR samples of H1N1 were (141.9±47.3), (417.6±119.3), (149.1±37.5), (6.2±1.6), (535.6±104.7) ppb respectively, the Mean±SD of As, B, Pb, Sr and Zn in negative RT-PCR samples of HIV were (12.5±0.9), (169.8±35.2), (138.2±34.5), (8.12±1.3), (421.4±40.1) ppb respectively, the Mean±SD of As, B, Pb, Sr and Zn in negative RT-PCR samples of HBV were (122.3±21.6), (160.7±23.6), (40.9±8.5), (53.7±7.7), (1459.4±90.1) ppb respectively, the Mean±SD of As, B, Pb, Sr and Zn in negative RT-PCR samples of HCV were (4.9±1.8), (3.7±1.34), (123.2±31.7), (60.9±22.5), (180.2±55.6) ppb respectively. The As, B, Pb, Sr, Zn concentrations in all the RT PCR negative samples were above the permissible limit, and also, we found a positive correlation between As levels and viral immunity in HCV patients (≤0.05). Conclusion: These results indicated that an accumulation of metals, especially As, in the body for a long time provides immunity against many viral diseases (H1N1, HIV, HBV, and HCV). Keywords: Immune status, Immune Response, Toxicity, Metals